1998
DOI: 10.1159/000023898
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Histamine and Substance P in Immediate Allergic Responses in Guinea Pig Airways: Characterization of MDL 108,207DA, a Dual H<sub>1</sub> / NK-1 Receptor Antagonist

Abstract: Background: Histamine is a critical mediator of immediate hypersensitivity reactions. Sensory neuropeptides, such as substance P (SP), may also contribute to acute inflammatory responses. A compound which antagonizes both H1 and NK-1 receptors, such as MDL 108,207DA, may present a significant therapeutic advantage over pure antihistamines. Methods: The binding affinity of MDL 108,207DA for H1 and NK-1 receptors was evaluated and its potency of antagonism evaluated in vitro. The in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Few studies are published on the involvement of tachykinins in acute allergic responses in the airways. Antigen‐induced microvascular leakage revealed a role for substance P in the early allergic response [28]. Recently it was shown that toluene diisocyanate induces a rapid increase of substance P; 1 h after inhalation of toluene diisocyanate the number of substance P immuno‐reactive nerve fibres was already increased [29].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies are published on the involvement of tachykinins in acute allergic responses in the airways. Antigen‐induced microvascular leakage revealed a role for substance P in the early allergic response [28]. Recently it was shown that toluene diisocyanate induces a rapid increase of substance P; 1 h after inhalation of toluene diisocyanate the number of substance P immuno‐reactive nerve fibres was already increased [29].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of phytochemicals with a high affinity for more than one pharmacological target presents a great advantage. Multiple reports highlight the benefits of combining therapies for AR treatment [44], such as the inhibition of HR1 and NKR1 [45] or HR1 and CLR1 [46]. Therefore, we performed MD simulations to further analyze the ability of amentoflavone, alpha-tocotrienol, neoxanthin, and isorhamnetin 3-O-rutinoside to function as antagonists of the five selected targets.…”
Section: Molecular Docking Of Ud Database Against Ar Targetsmentioning
confidence: 99%